Photoperiodic regulation of the phospholipid molecular species composition in thoracic muscles and fat body of Pyrrhocoris apterus (Heteroptera) via an endocrine gland, corpus allatum - Hodkova, M; Berková, P; Zahradnícková, H (Journal of insect physiology, 2002)
In the conventional view, the winter adaptation of membrane lipids is induced by temperature decrease. We propose that winter remodelling of membranes in Pyrrhocoris apterus is triggered by short-day photoperiod before the temperature decrease and changes caused by cold temperature represent the later phase of adaptation. The induction of diapause by short-day photoperiod results in an accumulation of phosphatidylethanolamine (PE) molecular species with C(16:0)/C(18:2) acyl chains esterified to sn-1/sn-2 positions of glycerol at the expense of C(18:0)/C(18:2). Proportions of C(16:0)/C(18:2)-PE are enhanced in short-day compared to long-day insects in both thoracic muscles (TM, 15.0 vs. 8.2%) and fat bodies (FB, 24.9 vs. 13.6 %). Proportions of C(16:0)/C(18:2)-PE are further enhanced during cold acclimation (to 26.5% in TM, 33.6 % in FB) at the expense of a more saturated species, C(18:0)/C(18:1)-PE. These changes are less prominent in phosphatidylcholines (PC). The effect of photoperiod seems to be mediated via the corpus allatum. Long-day non-diapause females deprived of their corpus allatum have the phospholipid molecular species profile similar to that found in short-day diapausing females. While the acyl chain remodelling is regulated by both photoperiod and temperature, the head group composition is regulated by temperature only. Similar to most other organisms, the level of PE is higher (50.3 vs. 43.5% in TM, 44.3 vs. 37.8% in FB) and that of PC is lower (35.9 vs. 40.2% in TM, 41.6 vs. 46.1 % in FB) at cold temperatures (</=1 degrees C) compared to warm temperatures (>/=16 degrees C). In contrast to a general rule, the PE is less unsaturated than PC. In both TM and FB, proportions of unsaturated/unsaturated molecular species are consistently high in PC (56.3-67.5% in TM, 59.2-66.6% in FB), while they are consistently low in PE (19.1-26.7% in TM, 12.1-15.1% in FB). An adaptive significance of changes in the phospholipid composition for the low temperature and/or dehydration stress is discussed in relation to known physical properties of phospholipids.